164k views
1 vote
What is the sum of
(6x-27)=(3x+15)

2 Answers

5 votes
(6x-27)=(3x+15)
You have to isolate the variable so in anyway possible you have to get all number to one side and the variable and their coefficient to the other side.
3x/3x and 6x/6x leaves you with (2x-27)=(15)
Next you can add 27 to each side to get rid of the 27 with 2x leaving the problem at
2x=42
Then divide by two
42 divided by 2 is 21
So x=21
User Nussjustin
by
4.4k points
3 votes

Answer: 14

Step-by-step explanation: Step 1: Subtract 3x from both sides.

6x−27−3x=3x+15−3x

3x−27=15

Step 2: Add 27 to both sides.

3x−27+27=15+27

3x=42

Step 3: Divide both sides by 3.

3x

3

=

42

3

User Brownbay
by
4.4k points